2019
DOI: 10.1177/0972753120912913
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dystrophin Gene Mutations in Neuropsychological Domains of DMD Boys: A Longitudinal Study

Abstract: Background: Duchenne Muscular Dystrophy (DMD) is a fatal muscular dystrophy of pediatric population coupled with other secondary comorbidities including mental retardation and neuropsychological impairments. Mutation location in the dystrophin gene, have been associated with neuropsychological functioning in DMD. Purpose: We investigated temporal changes in the neuropsychological functioning of DMD subjects, hitherto understudied. Methods: Subjects with suspected DMD were enrolled according to the ethical gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(46 reference statements)
1
4
0
2
Order By: Relevance
“…This cross-sectional study also reported, for the first time, that cognitive quotients and pattern of functioning showed no change with age. These findings have subsequently been confirmed in other cohorts [ 2 , 3 , 4 , 5 ] and the assumption that cognitive function does not change over time has become commonly accepted. Hellebrekers et al [ 6 ] reported a longitudinal follow-up study on verbal span and processing speed in Duchenne boys and found a developmental stagnation in verbal-span capacity, irrespective of normal processing speed, appearing more pronounced in patients missing Dp427 and Dp140.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…This cross-sectional study also reported, for the first time, that cognitive quotients and pattern of functioning showed no change with age. These findings have subsequently been confirmed in other cohorts [ 2 , 3 , 4 , 5 ] and the assumption that cognitive function does not change over time has become commonly accepted. Hellebrekers et al [ 6 ] reported a longitudinal follow-up study on verbal span and processing speed in Duchenne boys and found a developmental stagnation in verbal-span capacity, irrespective of normal processing speed, appearing more pronounced in patients missing Dp427 and Dp140.…”
Section: Introductionsupporting
confidence: 58%
“…Several cross-sectional studies have previously reported that cognitive function does not significantly change over time [ 2 , 3 , 4 , 5 ]. Longitudinal assessments in our cohort confirm that the mean changes in a large cohort of 70 DMD boys was relatively small (−2.99 points).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report deficits in verbal intelligence quotient 12 as a part of general intelligence and non-verbal memory, executive functions 13 , attention, visuo-construction ability 14 , problems with narrative, linguistic and reading skills 15 . We have also reported a non-progressive deterioration of neuropsychological domains 16 . Conflicting and variable degree of cognitive output in DMD necessitates understanding of a common cognitive domain for designing rehabilitation strategies 17 .…”
Section: Introductionmentioning
confidence: 53%
“…The presence of non-progressive mental retardation is a prominent clinical feature in DMD ( Bresolin et al, 1994 ). We have also reported non-progressive intellectual and neuropsychological deficits in our DMD cohort ( Tyagi et al, 2019b ).…”
Section: Introductionmentioning
confidence: 61%